Sustainable Purposed Marketing on Brand Loyalty, Competitive Advantage, and Customer Loyalty - Dadang Supriatna; Dadang Munandar; Putut Raka Santosa (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
The goals of this study are to know the influence of sustainable and purpose driven marketing on brand loyalty and its impact on competitive advantage and customer loyalty. Researchers use a quantitative approach and survey method. Respondents as much as 96 persons, drawn from the population used Cochran Formula, are the consumers of Major Indonesian Online Shops, such as Shopee, Lazada, Tokpedia and Bukalapak in Bandung City. Results of the study are as follows: First, Sustainability and Purpose Driven Marketing affects significantly Brand Loyalty simultaneously. Second, Sustainability affects significantly Brand Loyalty partially. Third, Purpose Driven Marketing affects significantly Brand Loyalty partially. Fourth, Brand Loyalty affects significantly Competitive Advantage partially. Fifth, Brand Loyalty affects significantly Customer Loyalty partially. Sixth, Sustainability and Purpose Driven Marketing affects significantly Competitive Advantage through Brand Loyalty simultaneously. Seventh, Sustainability affects significantly Competitive Advantage through Brand Loyalty. Eighth Purpose Driven Marketing affects significantly Competitive Advantage through Brand Loyalty. Ninth, Sustainability and Purpose Driven Marketing affects significantly Customer Loyalty through Brand Loyalty simultaneously. Tenth, Sustainability affects significantly Customer Loyalty through Brand Loyalty partially. Eleventh, Purpose Driven Marketing affects significantly Customer Loyalty through Brand Loyalty partially. Keywords: sustainability; purpose driven marketing; brand loyalty; competitive advantage; customer loyalty